The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1038/sj.bjp.0702684
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5‐HT1B receptors in collar‐induced hypersensitivity to 5‐hydroxytryptamine of the rabbit carotid artery

Abstract: 1 In humans intimal thickening is a prerequisite of atherosclerosis. Application of a silicone collar around the rabbit carotid artery induces an intimal thickening but in addition it increases the sensitivity to the vasoconstrictor action of serotonin (5-hydroxytryptamine, 5-HT). The 5-HT receptors involved in collar-induced hypersensitivity to 5-HT were investigated using several agonists and antagonists. 2 One week after placement of collars around both carotid arteries of anaesthetized rabbits, rings (2 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
(78 reference statements)
2
13
0
Order By: Relevance
“…A 2-mm segment was cut from each collar-wrapped carotid artery and mounted in organ chambers filled with 10 ml of physiological salt solution (118 mM NaCl, 4.7 mM KCl, 2.5 mM CaCl 2 , 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 , 25 mM NaHCO 3 , 0.025 mM CaEDTA, and 11.1 mM glucose) at 37°C, continuously aerated with 95% O 2 /5% CO 2 for force measurements at 6 g loading tension as described previously (Geerts et al, 1999). Tension was measured isometrically with a Statham UC2 force transducer (Gould, Cleveland, OH) connected to a data acquisition system (Moise 3; EMKA Technologies, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…A 2-mm segment was cut from each collar-wrapped carotid artery and mounted in organ chambers filled with 10 ml of physiological salt solution (118 mM NaCl, 4.7 mM KCl, 2.5 mM CaCl 2 , 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 , 25 mM NaHCO 3 , 0.025 mM CaEDTA, and 11.1 mM glucose) at 37°C, continuously aerated with 95% O 2 /5% CO 2 for force measurements at 6 g loading tension as described previously (Geerts et al, 1999). Tension was measured isometrically with a Statham UC2 force transducer (Gould, Cleveland, OH) connected to a data acquisition system (Moise 3; EMKA Technologies, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Recently, 5-HT 1B receptors have also been implicated as mediators of 5-HT-induced vasoconstriction. The 5-HT 1B receptor has been shown to mediate contraction in human pulmonary artery, 5 rat pulmonary artery, 6 human coronary artery, 7 human cerebral artery, 8 rabbit carotid artery, 9 rabbit ear artery, 10 rabbit renal artery, 11 and rat tail artery. 12 The 5-HT 1B receptor appears to be the predominant receptor mediating 5-HT-induced contraction in the human cerebral arteries.…”
mentioning
confidence: 99%
“…For the first time, we showed that lacidipine could reverse the increased sensitivity to 5-HT in early atherosclerosis. The increased expression of 5-HT-1B receptor is reported to be involved in hypersensitivity to 5HT-induced contraction in collared arteries (Geerts et al, 2000, Geerts et al, 1999) as in pathological conditions (Kaumann & Levy, 2006) and stimulation of the migration and proliferation of SMC (Fanburg BL, 1997, Sharma et al, 1999). 5HT-1B receptor induced hypersensitivity is reported due to sensitization of the contractile myofilaments to Ca ++ via voltage-dependent Ca ++ channels (Hill et al, 2000).…”
Section: Discussionmentioning
confidence: 99%